Statyka Rusztów Płaskich - Nowacki, Witold (Engineering Transactions, 1954)
The subject of this paper is the application of the deformation method, widely used in the statics of flat frames, for frame systems loaded with forces perpendicular to the plane of the frame or with moments, whose vectors lie in the plane of the system. Systems of this kind are called flat gridwork systems.These systems are applied extensively in reinforced concrete structures such as broken line girders, annular beams, flat frames loaded by forces caused by the wind, etc.In the first section a general method of solution is given, while the second section deals with the formulae of general transformation for curved and broken line bars.In the following sections the canonical equation of the above method is expanded. This is then reduced to more specialized forms which are typical for building technique.Finally, in the last section, the deformation methods are extended toinclude gridwork systems resting on an elastic foundation.